L-Citrulline Supplementation in Postmenopausal Women: Evidence from Clinical Trials - Panggabean, Satya Alfarisma; Mumtazah, Intan Syarifatin; Arifianti, Laily Nur Rachmah Wati Putri; Muhammad, Rajasawardana Fadhli (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: Postmenopausal women are at heightened risk for cardiovascular and muscular health decline due to endothelial dysfunction, arterial stiffness, and reduced nitric oxide (NO) bioavailability. L-Citrulline, a precursor to L-arginine and NO, has emerged as a promising supplement to counter these age-related vascular and musculoskeletal impairments. Material and Methods: A systematic review of randomized controlled trials was conducted in accordance with PRISMA guidelines using PubMed, ScienceDirect, and Cochrane Library databases. Eligible studies assessed oral L-Citrulline supplementation in postmenopausal women, with outcomes categorized into: vascular function (blood pressure, flow-mediated dilation [FMD], pulse wave velocity [PWV]); muscle function and oxygenation (tissue saturation index [TSI], oxy-/deoxyhemoglobin [O₂Hb/HHb], strength, lean mass, exercise performance); and autonomic regulation (heart rate variability [HRV]). Methodological quality was evaluated using the Cochrane Risk of Bias Tool 2.0. Results: L-Citrulline supplementation, administered in doses ranging from 6 to 10 g/day over 4–8 weeks, significantly improved cardiovascular outcomes, including reductions in brachial and aortic systolic/diastolic blood pressure, pulse pressure, and augmentation index. Flow-mediated dilation (FMD) improved by up to 2.7%, and nitric oxide availability increased, indicating enhanced endothelial function. Additionally, L-Citrulline improved muscle oxygenation during exercise, increased leg lean mass and strength when combined with low-intensity resistance training, and favorably modulated autonomic function through improved heart rate variability. Conclusion: L-Citrulline supplementation demonstrates substantial potential for improving vascular health, enhancing muscle oxygenation and strength, and restoring autonomic balance in postmenopausal women. These findings support its use as a non-pharmacological strategy to mitigate age-related declines in cardiovascular and muscular function.